Profiles of Traumatic Stress Symptoms in Children Exposed to Intimate Partner Violence - Galano, Maria M. (Journal of interpersonal violence, 2021)
Childhood exposure to intimate partner violence (IPV) is associated with a host of problems, including the development of posttraumatic stress symptoms (PTSS). PTSS include a wide range of unique symptomatology and as a result, clinical presentations of PTSS can vary in both distribution and overall number of symptoms. Work in child and adolescent samples has largely focused on factors predicting the total number of symptoms (i.e., symptom severity), with less work focused on both patterns of symptom number and distribution. Furthermore, few studies have examined how functional impairment varies in relation to PTSS presentation. The goal of the current study is to (a) document patterns of PTSS severity and distribution in children with histories of witnessing IPV, (b) examine the factors that predict different PTSS presentations, and (c) investigate how PTSS presentation is associated with functional impairment. Data for this study were drawn from a sample of 236 children between the ages of 4 and 12 years and their mothers who had experienced recent IPV. Families reported high levels of IPV in the past year, and children reported moderate levels of PTSS. A latent profile analysis of PTSS revealed that three profiles were the best-fitting model for the data. The three profiles were differentiated between low, moderate, and high levels of PTSS, and membership in the profiles varied by children’s age and trauma history. The results of this study give important information about the potential development of PTSS as well as clinically useful information about the relationship between children’s PTSS and their functioning following exposure to IPV.